Farmers' knowledge, perceptions and management of diseases affecting sweet potatoes in the Lake Victoria Zone region, Tanzania. (June 2015) - Adam, Rahma Isaack; Sindi, Kirimi; Badstue, Lone
Abstract: The purpose of this study was to assess farmers' knowledge, perception and management of sweet potato (SP) diseases, and to determine factors associated with farmers' satisfaction with sweet potato planting material in Mwanza and Mara sites within the Lake Victoria Zone region of Tanzania. We used multiple methods and data sources, principally a survey of 621 households spread across nine districts, and in-depth interviews with farmers in three villages located in three different districts. Our study revealed four main findings. Firstly, we found that although farmers were able to identify unhealthy SP plants, they were unable to tell the specific type of disease affecting the plants both from direct and photographic observations. Secondly, there exists considerable heterogeneity in the way farmers manage unhealthy plants in the field; some farmers were observed to follow management methods prescribed by plant pathologists, while others used traditional methods of managing a diseased plant. Thirdly, the following three factors were found to be the determinants of farmers' knowledge and management of SP diseases and plant root damage: (i) farmers' training in SP production and management; (ii) the number of plots which the woman of the household has control over; and (iii) household membership to a crop production association. Lastly, the location of farms is a strong determinant of farmers' satisfaction with SP vines; residing in areas in which sweet potato vines are widely available and in a village that is accessible by a primary road or tarmac road increases a farmer's satisfaction with sweet potato vines that are available in the farmers' farm during planting time. Highlights: We assessed farmers' knowledge of sweet potato (SP) diseases. We assessed factors associated with farmers' satisfaction with SP vines. Farmers were not necessarily able to tell the specific type of plant disease affecting SP. Training with SP production aided farmers to have knowledge of SP diseases. Farmers' location determines farmers' satisfaction with SP vines.